Immunological Characteristics of Alternative Splicing Profiles Related to Prognosis in Bladder Cancer - Ye, Fangdie; Liang, Yingchun; Cheng, Zhang; Liu, Yufei; Hu, Jimeng; Li, Weijian; Chen, Xinan; Gao, Jiahao; Jiang, Haowen (Frontiers in Immunology, 2022)
Several studies have found that abnormal alterative splicing (AS) events are related to carcinogenicity. However, the association between genetic variation in AS events and bladder cancer susceptibility has not been extensively explored. Here, we downloaded AS event signatures, transcriptome profiles, and matched clinical information from The Cancer Genome Atlas (TCGA) database. The least absolute shrinkage and selection operator (LASSO) and multivariate Cox regression analyses were conducted to build prognostic risk models. Single-sample (ssGSEA), ESTIMATE, and the CIBERSORT algorithms were used to evaluate the tumor microenvironment status. CCK8, cell culture scratch, and transwell invasion assays and flow cytometry were used to verify the reliability of the model. We found 2751 prognostic-related AS events, and constructed a risk model with seven prognostic-related AS events. The overall survival rate of patients in the high-risk group was lower than that in the low-risk group. Univariate and multivariate Cox regression analyses showed that the risk score was an independent prognostic factor. Risk score was also closely related to alterations in immune cell infiltration and immunotherapeutic molecules, indicating its potential as an observation of immune infiltration and clinical response to immunotherapy. In addition, DYM could be a promising prognostic factor for bladder cancer. Our study provided an indispensable reference for further investigation of the role of AS events in the tumor microenvironment and immunotherapy efficiency, and rendered personalized prognosis monitoring for bladder cancer.